Terrorism vs bioterrorism: which one is the scariest? / Nor Anita Abdullah and Rohani Abdul Rahim - Abdullah, Nor Anita; Abdul Rahim, Rohani (2014)
Over the centuries man has been warned about the threats of terrorism. It represents serious threat to the society and physically appeared as type of violence in form of war and attack. It also becomes major concern and challenge to whole life of people in the public security. Unlike terrorism, another threat which also demonstrates the threat to the whole life of people and increase the level of fear and panic was introduced as bioterrorism, a new form of threat. There was a belief that bioterrorism will not happen too soon and under prediction. Thus, the threat seems to be ignored and denied. However, the event of 11 September, 2001 had changed everything and it turns out to be a denial to the belief. Thus, this paper aims to discuss the aspect of terrorism and bioterrorism in the context of threats and challenges to the public society by looking into the differences and similarities between both especially in Malaysian context. This paper also attempts to give a look at the Malaysian experience with regard to the both.